Are hotel companies creditworthy? The case of Portuguese hospitality industry - Pãozinho, Ricardo (2020)
The hospitality industry achieved an important place in modern economies, namely in terms of the contribution to the GDP and for direct and indirect employment. Considering that, this paper aims to highlight the hotel companies’ level of solvency, as a sustainability factor in an extremely competitive sector. The main structure ratios of Portuguese Hotels in the 2010-2017 period will be analyzed; data was collected on July 4, 2019, on the SABI platform and the original sample is composed by 2161 hotel companies registered with two economic activity codes (CAE), “55111 - Hotels with restaurant” and “55121 - Hotels without restaurant”. The structure ratios, also known as debt ratios, highlight the importance of financing sources (resources), as well as the way in which financing is applied (applications). On the other hand, capital raising by companies, whether they are from the hospitality sector or not, should be carried out at the lowest cost in order to maximize their value. For the hotelier, it is essential to have his company balanced in the medium and long term; that is the reason why the investment coverage ratio, the fixed assets coverage ratio, the financial autonomy ratio and the solvency ratio were considered in the analysis. It is expected to obtain results that help hospitality managers understand the importance of the solvency and to guide the management for the financial sustainability in the medium and long term.